Variceal gastrointestinal bleeding: epidemiology, pathogenesis, management and prophylaxis - Padilla-Machaca, P. Martin (2025)
Variceal gastrointestinal bleeding is one of the main complications of portal hypertension in patients with cirrhosis. It affects those with decompensated cirrhosis, and its occurrence marks a turning point in the progression of liver disease. Despite therapeutic advances, challenges remain in comprehensive management, particularly in resource-limited settings. Treatment aims to control active bleeding, prevent early rebleeding, and reduce mortality. This review summarizes recent evidence on the pathophysiology, diagnosis, and updated management of variceal gastrointestinal bleeding, including emerging strategies such as early vasoactive therapy, rational use of transfusions, antibiotic prophylaxis, and the key role of timely endoscopy. It also highlights the importance of identifying clinically significant portal hypertension to prevent complications and improve clinical outcomes.